Development of unmanned aerial vehicle (UAV) based high altitude balloon (HAB) platform for active aerosol sampling - Lateran, S.; Sedan, M. F.; Mohd Harithuddin, Ahmad Salahuddin; Md Ali, Syaril Azrad (Institute of Physics Publishing, 2016)
The knowledge on the abundance and diversity of the minute particles or aerosols in the earth's stratosphere is still in its infancy as aerosol sampling at high-altitude still possess a lot of challenges. Thus far, high-altitude aerosol sampling has been conducted mostly using manned flights, which requires enormous financial and logistical resources. There had been researches for the utilisation of high altitude balloon (HAB) for active and passive aerosol samplings within the stratosphere. However, the gathered samples in the payload were either brought down by controlling the balloon air pressure or were just dropped with a parachute to slow the descend speed in order to reduce the impact upon landing. In most cases, the drop location of the sample are unfavorable such as in the middle of the sea, dense foliage, etc. Hence a system that can actively sample aerosols at high-altitude and improve the delivery method in terms of quality and reliability using unmanned aerial vehicle (UAV) is designed and tested in this study.